2001
DOI: 10.1002/1522-2683(200101)22:1<165::aid-elps165>3.0.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

Reduced proteolysis of surfactant protein A and changes of the bronchoalveolar lavage fluid proteome by inhaled α1-protease inhibitor in cystic fibrosis

Abstract: In cystic fibrosis (CF), the chronic neutrophilic inflammation of the airways results in proteolytic degradation of lung tissue early in the course of the disease. Inhalation of alpha 1-protease inhibitor (alpha 1-PI) may restore the protease-antiprotease imbalance and thus lead to less tissue damage. To monitor its impacts on bronchoalveolar lavage (BAL) fluid protein pattern (proteome) and on surfactant protein A (SP-A), eight young adults with CF inhaled 100 mg of alpha 1-PI twice daily over eight weeks. BA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
31
0
2

Year Published

2001
2001
2009
2009

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 25 publications
2
31
0
2
Order By: Relevance
“…Chronic airway inflammatory diseases, such as cystic fibrosis, have also been associated with decreased SP-A and SP-D (43), and have been found to have high numbers of airway apoptotic cells (26). Protease/ antiprotease imbalance in these diseases may also contribute to impaired collectin-mediated removal of apoptotic cells, either through direct degradation of collectins (44), or through degradation of their receptor. In this vein, we have observed that elastase cleaves calreticulin and CD91 (our unpublished observation), as well as the phosphatidylserine receptor (26).…”
Section: Discussionmentioning
confidence: 99%
“…Chronic airway inflammatory diseases, such as cystic fibrosis, have also been associated with decreased SP-A and SP-D (43), and have been found to have high numbers of airway apoptotic cells (26). Protease/ antiprotease imbalance in these diseases may also contribute to impaired collectin-mediated removal of apoptotic cells, either through direct degradation of collectins (44), or through degradation of their receptor. In this vein, we have observed that elastase cleaves calreticulin and CD91 (our unpublished observation), as well as the phosphatidylserine receptor (26).…”
Section: Discussionmentioning
confidence: 99%
“…The predominance of the LMW (¡20 kD) proteins in CF BALF may at least partly be due to an accumulation of degraded structure, defence, bacterial or in¯ammatory proteins. This is in accordance with the data of a previous report by the authors, where an 8 week inhalation of a 1 -PI in CF patients led to a signi®cant reduction in the number and Vol% of these LMW proteins ¡20 kD [20]. Various proteins were seen in CF, which were not present in controls and vice versa.…”
Section: Discussionmentioning
confidence: 99%
“…This study in CF patients with an FEV1 of .60% of the predicted value clearly demonstrated free HLE in the alveolar compartment, which was neutralised dose-dependently and reached free anti-HLE capacity in some cases. In another smaller study, treatment with a 1 -AT in the lower dose range led to reduced levels of total protein, numbers and amounts of proteins with a molecular weight of ,20 kDa, and degradation products of SP-A [137]. In the latter study, no effect of a 1 -AT on surfactant convertase, an alveolar enzyme hypothesised to be inhibited by serine protease inhibitors, was noted [138].…”
Section: Inhibition Of Free Elastase By Inhaled a 1 -At Inmentioning
confidence: 99%